Seasonal vegetative growth of different age branches of conilon coffee tree / Crescimento vegetativo sazonal em ramos de diferentes idades do cafeeiro conilon - José Cochicho Ramalho; Marcelo Gabeto Silva; Henrique Duarte Vieira; Fábio Luiz Partelli (Semina: Ciências Agrárias, 2010)
The seasonal pattern of vegetative growth is an important feature for evaluation of crop status and its management. The aim of this work was to evaluate the seasonality of vegetative growth of Conilon coffee tree (Coffea canephora Pierre) and its relation with climate variables. The evaluation of vegetative growth rates of three groups of plagiotropic branches and one group of orthotropic branches was performed along one year, in Rio Janeiro state, Brazil. The vegetative growth rates of the branches varied along the period of evaluation, and it seems to be related to the minimum air temperature (in the low growth phase). Higher growth rates were observed when the average of minimum air temperatures was higher than 17ºC and the average of the maximum temperatures lower than 31.5ºC. Below 17ºC the growth rate declined. The branches’ growth patterns appeared to be similar, but the plagiotropic branches of different ages presented different rates in the same period of the year, indicating that seasonal growth studies should not be based on a single branch group with the same age. O padrão do crescimento sazonal do cafeeiro é um importante auxiliar na avaliação do estado fisiológico e no manejo da cultura. O objetivo do estudo foi avaliar o crescimento vegetativo em Coffea canephora Pierre cv. Conilon e relacionar com fatores climáticos, tendo por base o crescimento de ramos ortotrópicos e plagiotrópicos com diferentes idades. Marcaram-se três grupos de ramos plagiotrópicos e um de ramos ortotrópicos, cuja avaliação de taxa de crescimento foi efetuada durante um ano no Estado do Rio de Janeiro. A taxa de crescimento varia ao longo do ano, o que parece estar relacionado com a temperatura mínima do ar (na fase de baixo crescimento). Foi observada taxa mais elevada quando a média da temperatura mínima do ar foi superior a 17ºC e a média das temperaturas máximas inferior a 31,5ºC. Abaixo de 17ºC a taxa de crescimento dos ramos diminuiu. O padrão sazonal de crescimento dos ramos é semelhante, contudo, os ramos plagiotrópicos de diferentes idades apresentam taxas de crescimento diferentes no mesmo período do ano. Assim, estudos sobre o crescimento vegetativo sazonal dos ramos não deve se basear apenas num grupo de ramos com idades similares.